Empowerment Model Based on Physical Training, Religion, Local Wisdom, and Community Participation to Improve Income and Physical Health in The Religious Tourism Village of Penyengat Island - Cahyono, Korisnur; Junianto, Sony (Journal Coaching Education Sports, 2025)
This study aims to analyze the influence of the level of community participation and local wisdom on increasing community income in the Religious Tourism Village of Penyengat Island, with religion as a moderating variable. This village is one of the religious tourism destinations that has a rich Islamic culture and strong Malay historical heritage. This study uses a quantitative approach with a survey method to the local community, and the data is analyzed using the PLS-SEM model. The results of the study indicate that community participation and local wisdom have a direct positive and significant effect on increasing income. However, religion as a moderating variable does not always strengthen this influence. Religion is proven to significantly mediate the relationship between community participation and income, but actually weakens this influence because of the emphasis on spiritual values, simplicity, and social norms that can limit economic activities. Meanwhile, the role of religion in mediating the relationship between local wisdom and community income is not significant. The implications of these findings indicate the need for a sensitive approach to religious values ​​in the development strategy of religious tourism villages. The integration of spiritual values ​​within the economic framework must be strategically designed in order to encourage synergy between spirituality and economic welfare.